Redescription of Desertoniscus taschkentensis (Verhoeff, 1930) and description of Desertoniscus schmalfussi n. sp. (Isopoda: Oniscidea) - Gmkashani@Gmail.com, Ghasem M.; Allspach, Andreas (Zootaxa, 2012)
Desertoniscus schmalfussi n. sp. is described, D. taschkentensis (Verhoeff, 1930) formerly considered as Protracheonis-cus taschkentensis is redescribed and a lectotype is designated, and their diagnostic characters are figured. Desertoniscusschmalfussi n. sp. differs from all other species of the genus in having long setae on the apex of the male pleopod endopodite I and in having male pereiopod VII carpus with a distinct ridge on the dorsal margin.